Analisis Penerapan Dan Fungsi Algoritma Pemrograman Pada Komputer - Vina Alliana; Yahfizham Yahfizham (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
Over time, the progress of science, technology and information is growing very rapidly. One of the things related to this problem is that the children of the nation must now master and study the developing science and technology. Utilizing science technology is now very important. The computer is one example of a technological tool that can be used. Regarding computers, we must first study in detail about programming algorithms that have applications and functions for us in education and everyday life. The purpose of writing this article is to examine the application and function of programming algorithms. Then the writing of this article use the literature study method and library research, namely by studying systematically and structured about programming algorithms. Data collection is done by online books or offline books, reputable scientific journals and sources from Google Scholar, Digital Library, website research and so on. The result of writing this article is that the application or presentation of programming algorithms can be seen in examples of application in mathematics. Writing an algorithm is not bound by a certain rule, but it must be clear what it means for each step of the algorithm. Many functions are very important in programming algorithms. The main function of programming algorithms is to solve a problem. This algorithm is an important thing in the activity of making a program.